The Role of Soviet Union Assistance to Indonesia in the Preparation of the IV Asian Games Jakarta in 1959-1962 - M. Irfan Yunus (Tarikhuna: Journal of History and History Education, 2025)
This article examines the assistance provided by the Soviet Union to Indonesia during the preparation for the IV Asian Games in Jakarta in 1962 and the subsequent impact of that assistance on the hosting of the Games. The research employs the historical method, which consists of five stages: Topic Selection, Source Collection (Heuristics), Verification, Interpretation, and Historiography. The data sources for this research are divided into Primary and Secondary Sources. Primary Sources were obtained from various archives related to the Indonesian-Soviet partnership and the preparation for the IV Asian Games, accessible at the National Archives of the Republic of Indonesia (ANRI). Furthermore, Primary Sources also include contemporary newspapers and magazines that reported on the bilateral relationship between Indonesia and the Soviet Union, as well as news concerning the IV Asian Games. Secondary Sources utilized in this study include relevant research and books discussing the Indonesia-Soviet Union relationship and the Asian Games. The findings of this research indicate that the assistance provided by the Soviet Union government to the Indonesian government was vital in the successful organization of the IV Asian Games in 1962, particularly concerning the construction of the sports complex that served as the venue for the largest multi-sport event on the Asian continent. This construction received funding and technical assistance from the Soviet Union. Furthermore, the preparation for the IV Asian Games illustrates the close diplomatic relationship between Indonesia and the Soviet Union, especially during the period of Guided Democracy under the administration of President Sukarno.